Open science: a revolution in sight?. Issue 4 (21st November 2016) - Rentier, Bernard
Abstract : Purpose: This paper aims to describe the evolution of scientific communication, largely represented by the publication process. It notes the disappearance of the traditional publication on paper and its progressive replacement by electronic publishing, a new paradigm implying radical changes in the whole mechanism. It aims also at warning the scientific community about the dangers of some new avenues and why, rather than subcontracting an essential part of its work, it must take back full control of its production. Design/methodology/approach: The paper reviews the emerging concepts in scholarly publication and aims to answer frequently asked questions concerning free access to scientific literature as well as to data, science and knowledge in general. Findings: The paper provides new observations concerning the level of compliance to institutional open access mandates and the poor relevance of journal prestige for quality evaluation of research and researchers. The results of introducing an open access policy at the University of Liège are noted. Social implications: Open access is, for the first time in human history, an opportunity to provide free access to knowledge universally, regardless of either the wealth or the social status of the potentially interested readers. It is an essential breakthrough for developing countries. Originality/value: Open access and Open Science in general must be considered as common values that should be shared freely. Free access to publicly generated knowledge should be explicitly included in universal human rights. There are still a number of obstacles hampering this goal, mostly the greed of intermediaries who persuade researchers to give their work for free, in exchange for prestige. The worldwide cause of Open Knowledge is thus a major universal issue for the twenty-first century.